Theoretical review about social audit and its relationship with financial statements audit - Madera Morillo, Tania Sofía; Flores Gómez, Aída Mercedes (SATHIRI, 2021)
This article deals with a review of the literature with the relationship of Social Audit and Financial auditing, framed in the analysis of social auditing and its relationship with auditing of financial statements; considering the need not only for organizations to determine the reasonableness of their financial statements, in economic terms, but also the importance of identifying whether the social effects of business activities have benefited society, or whether the operations of the line of business have generated economic, environmental or social damage to the community and to the main activities of the business. The methodology applied in this research was qualitative, so as to allow the identification of the evolution of concepts, approaches, regulations and application of the two aforementioned branches of the audit. This review of the literature allows the relevance of the Financial and Social Audit examination carried out in any entity, public or private, since it allows users to have a broader vision of the business reality, and the assurance that the recommendations and conclusions presented in the audit reports reflect reliability, not only in the financial area, but also in the social area, which implies that the social audit complements and is directly related to the financial audit since it allows verifying that the economic results and the form how the resources were managed were or were not adequate, establishing better internal and external control that will benefit the entity and society in general.